Phacoemulsification with combination of CTR and Iris Hook in Subluxated Cataract - Muhammad Abdurrauf; Dicky Hermawan (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Purpose: To report a management of challenging case of phacoemulsification in cataract with subluxated lens. Methods: A 63 male patient referred to RSDS with secondary lens induced glaucoma and cataract with subluxation around 210O on left eye. Patient was planned to undergone Phacoemulsification with combination of CTR and Iris Hook for lens extraction. Result: Postoperative result is satisfactory with minimal corneal edema. After 6 weeks of follow-up uncorrected vision is 5/8 with correction of S+0.25 became 5/5 and IOP is stable at 17 mmHg and the IOL was in placed in the bag and well centered. Conclusion: Phacoemulsification with iris hooks combined with CTR is one of surgery option that is safe and widely attainable for cataract with subluxated lens.